The influence of weather on catches of ducks in Steeple Decoy, Essex, in 1714-1726 - Boyd, Hugh (Wildfowl, 1995)
Over 50,000 immigrant Wigeon, Mallard and Teal were caught at a decoy in Essex built in 1714 and apparently abandoned after 13 seasons. Though there were measurements of temperature and rainfall in England at that time, there were no instrumental weather records from Scandinavia and northwest Russia, the most likely principal source of the Teal and Wigeon. Variations in English summer weather had no detectable effects on the numbers of ducks caught in autumn and early winter. Wigeon and Teal arrived earlier than they do now, yet more were taken in seasons when the winter months were cold. More ducks, especially Mallard, were caught in seasons when rainfall from September to February was below average. An increase in the sale price of ducks after the catches had declined suggests that a regional scarcity of ducks, rather than poor use of the decoy, may have brought about the decline. Using annual tree-ring widths from Finland and the Polar Urals as proxies for summer weather in their breeding ranges, 49% of the variation in the catches of Teal and 27-32% in those of Wigeon seem attributable to differences in summer conditions, with larger catches of Teal and Wigeon in years of strong tree growth in Fennoscandia. In the context of climactic change, there is a need for studies of long-term changes in wildfowl populations and their sensitivity to climactic variations.